2013
DOI: 10.1073/pnas.1308510110
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of Argonaute–GW182 protein interactions

Abstract: MicroRNAs (miRNAs) guide Argonaute (Ago) proteins to target mRNAs, leading to gene silencing. However, Ago proteins are not the actual mediators of gene silencing but interact with a member of the GW182 protein family (also known as GW proteins), which coordinates all downstream steps in gene silencing. GW proteins contain an N-terminal Ago-binding domain that is characterized by multiple GW repeats and a C-terminal silencing domain with several globular domains. Within the Ago-binding domain, Trp residues med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 45 publications
7
91
0
Order By: Relevance
“…In agreement with our results, a previous study demonstrated that S387 phosphorylation in HeLa cells increased Ago2‐GW182 binding and had no effect on miRNA loading (Horman et al , 2013). While S387 is situated between the PAZ and MID domains of Ago2, GW182 associates with the PIWI domain towards the C‐terminus of Ago2 (Pfaff et al , 2013), suggesting that phosphorylated S387 is unlikely to contribute to the GW182 binding site directly. A recent study provides an explanation for this by demonstrating that the LIM‐domain protein LIMD1 binds both GW182 and S387‐phosphorylated Ago2 in HeLa cells and stabilises the interaction between Ago2 and GW182 in response to Ago2 phosphorylation (Bridge et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, a previous study demonstrated that S387 phosphorylation in HeLa cells increased Ago2‐GW182 binding and had no effect on miRNA loading (Horman et al , 2013). While S387 is situated between the PAZ and MID domains of Ago2, GW182 associates with the PIWI domain towards the C‐terminus of Ago2 (Pfaff et al , 2013), suggesting that phosphorylated S387 is unlikely to contribute to the GW182 binding site directly. A recent study provides an explanation for this by demonstrating that the LIM‐domain protein LIMD1 binds both GW182 and S387‐phosphorylated Ago2 in HeLa cells and stabilises the interaction between Ago2 and GW182 in response to Ago2 phosphorylation (Bridge et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The residues flanking the W residues mediate weak interactions, which are most likely nonspecific, as different amino acids are tolerated at these positions as long as they have a small side chain. However, in the context of full-length AGO proteins, not all W residues contribute equally to the affinity of the interaction [51][52][53][54][55][56][57][58]60 , indicating that the flanking regions influence binding in ways that are not completely understood.…”
Section: Interaction Of Gw182 Proteins With Ago Proteinsmentioning
confidence: 99%
“…Molecular recognition is predominantly restricted to the W residues, although the flanking residues contribute to the affinity of the interactions 26,28-30,58-60 . As a consequence of this mode of recognition, multiple W residues can mediate binding in a redundant manner and contribute to the affinity of the interaction through cooperativity and/or avidity effects 26,[28][29][30][51][52][53][54][55][56][57][58][59][60] . It is therefore likely that the stoichiometry of the complexes is not strictly defined and, to some extent, is determined by the relative affinities and concentrations of the interacting partners in the cell.…”
mentioning
confidence: 99%
“…In animals, target mRNA decay is accelerated by recruitment of the major deadenylases CCR4-NOT and PARN (Braun et al, 2011;Chekulaeva et al, 2011;Fabian et al, 2011). Recruitment of these complexes requires the adaptor protein GW182/TNRC6 that binds to CCR4-NOT and PARN and uses Trp side chains in intrinsically disordered regions to interact directly with hydrophobic pockets in AGO proteins (Schirle and MacRae, 2012;Pfaff et al, 2013). An exact counterpart of this mechanism is unlikely to exist in plants because no homolog of GW182/TNRC6 is present in plant genomes.…”
mentioning
confidence: 99%